Effect on HBs antigen clearance of addition of pegylated interferon alfa-2a to nucleos(t)ide analogue therapy versus nucleos(t)ide analogue therapy alone in patients with HBe antigen-negative chronic hepatitis B and sustained undetectable plasma hepatitis B virus DNA: a randomised, controlled, open-label trial. (March 2017) - Bourlière, Marc; Rabiega, Pascaline; Ganne-Carrie, Nathalie; Serfaty, Lawrence; Marcellin, Patrick; Barthe, Yoann; Thabut, Dominique; Guyader, Dominique; Hezode, Christophe; Picon, Magali; Causse, Xavier; Leroy, Vincent; et al.
Summary: Background: Findings from uncontrolled studies suggest that addition of pegylated interferon in patients with HBe antigen (HBeAg)-negative chronic hepatitis B receiving nucleos(t)ide analogues with undetectable plasma hepatitis B virus (HBV) DNA might increase HBs antigen (HBsAg) clearance. We aimed to assess this strategy. Methods: In this randomised, controlled, open-label trial, we enrolled patients aged 18–75 years with HBeAg-negative chronic hepatitis B and documented negative HBV DNA while on stable nucleos(t)ide analogue regimens for at least 1 year from 30 hepatology tertiary care wards in France. Patients had to have an alanine aminotransferase concentration of less than or equal to five times the upper normal range, no hepatocellular carcinoma, and a serum α fetoprotein concentration of less than 50 ng/mL, normal dilated fundus oculi examination, and a negative pregnancy test in women. Patients with contraindications to pegylated interferon were not eligible. A centralised randomisation used computer-generated lists of random permuted blocks of four with stratification by HBsAg titres (< or ≥2·25 log10 IU/mL) to allocate patients (1:1) to receive a 48 week course of subcutaneous injections of 180 μg per week of pegylated interferon alfa-2a in addition to the nucleos(t)ide analogue regimen or to continue to receive nucleos(t)ide analogues only. The primary endpoint was HBsAg loss at week 96 by intention-to-treat analysis. This trial is closed and registered withClinicalTrials.gov, numberNCT01172392 . Findings: Between Jan 20, 2011, and July 18, 2012, we randomly allocated 185 patients (92 [50%] to pegylated interferon and nucleos(t)ide analogues and 93 [50%] to nucleos(t)ide analogues alone). We excluded two patients from the pegylated interferon plus nucleos(t)ide analogues group from analyses because of withdrawal of consent (one patient) or violation of inclusion criteria (one patient). At week 96, loss of HBsAg was reported in seven (7·8%) of 90 patients in the pegylated interferon plus nucleos(t)ide analogues group versus three (3·2%) of 93 in the nucleos(t)ide analogues-alone group (difference 4·6% [95% CI −2·6 to 12·5]; p=0·15). 85 (94%) of 90 patients started pegylated interferon, three (4%) of whom had a dose reduction and 17 (20%) had an early discontinuation of pegylated interferon (seven [41%] for serious adverse events). Grade 3 and 4 adverse events were more frequent in the pegylated interferon plus nucleos(t)ide analogues group (26 [29%] grade 3 adverse events; 19 [21%] grade 4 adverse events) than in the nucleos(t)ide analogues-alone group (three [3%] grade 3; six [6%] grade 4). Interpretation: Addition of a 48 week course of pegylated interferon to nucleos(t)ide analogue therapy in patients with HBeAg-negative chronic hepatitis B with undetectable HBV DNA for a least 1 year was poorly tolerated and did not result in a significant increase of HBsAg clearance. Funding: Institut national de la santé et de la recherche médicale-Agence nationale de recherches sur le sida et les hépatites virales (France Recherche Nord&sud Sida-vih Hepatites).